Video Motion Graphic Sosialisasi Peran Orang Tua Dalam Pembelajaran Daring - Manurung, Fadoria; Albar, Deni (Fakultas Desain Universitas Komputer Indonesia, 2022)
This article highlights the role of parents in assisting online learning for elementary school students. In the distance learning process, many obstacles are found, especially for parents, because elementary grade students still need special attention. The object of this final project design is the parents of elementary school (SD) children. The solution to this problem is to invite and change the mindset of parents by informing the role of online learning mentoring for elementary school students. The purpose of the design is to persuade and provide socialization about the role of parents in mentoring, to understand learning styles and mentoring strategies when learning online, so that parents participate in mentoring children's learning. It is hoped that this design will provide benefits to the community, especially parents who are aware of the importance of assisting children's online learning while at home.